Dissecting dynamic plant virus synergism in mixed infections of poleroviruses, umbraviruses, and tombusvirus-like associated RNAs - Erickson, Anna; Falk, Bryce W. (Frontiers in Microbiology, 2023)
Mixed infections of a plant infecting polerovirus, umbravirus, and/or tombusvirus-like associated RNAs (tlaRNAs) produce unique virus disease complexes that exemplify ‘helper-dependence’ interactions, a type of viral synergism that occurs when a ‘dependent’ virus that lacks genes encoding for certain protein products necessary for it to complete its infection cycle can utilize complementary proteins encoded by a co-infecting ‘helper’ virus. While much research has focused on polerovirus-umbravirus or polerovirus-tlaRNA interactions, only recently have umbravirus-tlaRNA interactions begun to be explored. To expand on the limited understanding of umbravirus-tlaRNA interactions in such disease complexes, we established various co-infection pairings of the polerovirus turnip yellows virus (TuYV), the umbravirus carrot mottle virus (CMoV), and three different tlaRNAs—carrot red leaf virus aRNAs (CRLVaRNAs) gamma and sigma, and the TuYVaRNA ST9— in the model plant Nicotiana benthamiana, then investigated the effects of these different co-infections on tlaRNA systemic movement within the host, and on virus accumulation, and aphid and mechanical transmission of each of these viruses. We found that CMoV alone could support systemic movement of each of the tlaRNAs, making this the second report to demonstrate such an interaction between an umbravirus and tlaRNAs. We also report for the first time that CMoV could also impart mechanical transmissibility to the tlaRNAs sigma and ST9, and that co-infections of either of these tlaRNAs with both TuYV and CMoV increased the efficiency with which TuYV could be mechanically co-transmitted with CMoV.